A Cross-sectional Survey to Assess the Risk Factors of Cardiovascular Disease among College Students - K. Jafar Ali; Hansaram Suthar (Journal of the Scientific Society)
Introduction: Cardiovascular diseases (CVDs) are the number one cause of death globally which claim an estimated 17.9 million lives each year. It is a major cause of disability and premature death throughout the world and contributes substantially to the escalating costs of health care. Modification of risk factors has been shown to reduce mortality and morbidity in people with diagnosed or undiagnosed CVDs. Prior assessment is found to be helpful in predictions of absolute cardiovascular risks among young adults. Objectives: The objective of the study was to assess the risk factors of cardiovascular diseases among college students. Materials and Methods: A descriptive survey was conducted among 207 college students at Najath College of Science and Technology, Karuvarakundu, Kerala from October 10, 2019, to October 18, 2019. Convenient sampling method was used to select the samples. Structured risk factor assessment Pro forma and Biophysical measurements were used as tools. Result: The study identified 40.57% of students as at moderate risk and 5.31% were at high risk for developing cardiovascular diseases. The study reported that 6.2% of students were overweight, whereas 45% had elevated blood pressure. It was found that 64.25% of the students had a family history of chronic illnesses such as diabetes, hypertension, stroke, and obesity. The 8.21% of students were smokers out of these, 17.39% were using smokeless tobacco, whereas 31.88% were exposed to passive smoking and 12.56% of students were drinkers. In terms of physical activity, 62.31% of the students were sedentary. The food habits of 98.56% of students were nonvegetarian and 46.85% of them were consuming red meat. Conclusions: Periodic assessment and comprehensive health awareness would be helpful to modify unhealthy habits and minimize the risk of cardiovascular problems among the college students.